From Tumor Immunology to Immunotherapy in Gastric and Esophageal Cancer - Vrána, David; Matzenauer, Marcel; Neoral, Čestmír; Aujeský, René; Vrba, Radek; Melichar, Bohuslav; Rušarová, Nikol; Bartoušková, Marie; Jankowski, Janusz (International journal of molecular sciences, 2018)
Esophageal and gastric cancers represent tumors with poor prognosis. Unfortunately, radiotherapy, chemotherapy, and targeted therapy have made only limited progress in recent years in improving the generally disappointing outcome. Immunotherapy with checkpoint inhibitors is a novel treatment approach that quickly entered clinical practice in malignant melanoma and renal cell cancer, but the role in esophageal and gastric cancer is still poorly defined. The principal prognostic/predictive biomarkers for immunotherapy efficacy currently considered are PD-L1 expression along with defects in mismatch repair genes resulting in microsatellite instability (MSI-H) phenotype. The new molecular classification of gastric cancer also takes these factors into consideration. Available reports regarding PD-1, PD-L1, PD-L2 expression and MSI status in gastric and esophageal cancer are reviewed to summarize the clinical prognostic and predictive role together with potential clinical implications. The most important recently published clinical trials evaluating checkpoint inhibitor efficacy in these tumors are also summarized.
Keywords: mikrosatelitní repetice; antigeny CD274; kombinovaná terapie; microsatellite instability; Programmed Cell Death 1 Ligand 2 Protein; Immunotherapy; Humans; fenotyp; Combined Modality Therapy; Programmed Cell Death 1 Receptor; checkpoint inhibitors; nádory žaludku; epitelo-mezenchymální tranzice; Gene Expression; lidé; únik nádoru z imunitní kontroly; gastric cancer; exprese genu; Phenotype; Immunity; Epithelial-Mesenchymal Transition; antigeny CD279; B7-H1 Antigen; Animals; zvířata; immunotherapy; antigeny CD273; Stomach Neoplasms; Esophageal Neoplasms; mikrosatelitní nestabilita; imunita; imunoterapie; Microsatellite Instability; Microsatellite Repeats; esophageal cancer; nádory jícnu; Tumor Escape